Surface Treatment of Fly Ash for Improving the Tensile Strength of Fly Ash/Unsaturated Polyester Composites - Sugiman, Sugiman; Setyawan, Paryanto Dwi (UI Scholars Hub, 2013)
The paper presents the surface treatment of fly ashes using acid and alkali solution on the tensile strength of the fly ash/unsaturated polyester (UP) composites. Sulfuric acid (H2SO4), hydrofluoric acid (HF) and sodium hydroxide (NaOH) solution with concentration of 0%, 5%, 10%, 15%, and 20% (by weight) were used for surface treatment of fly ashes. Generally, the tensile strength of the treated fly-ash/UP composites shows a significant increase compared to the untreated fly ash. Of all surface treatments studied, the optimum tensile strength was obtained at a concentration of 10%. At this concentration, at a fly ash content of 30% (weight), the surface treatment using NaOH gave the highest tensile strength, approximately 18.69 MPa, or increased about 91% compared to the untreated fly ash. The morphology of fracture surfaces were evaluated using a scanning electron microscope (SEM). The fracture surfaces of the treated fly ash composite were rougher than that of the untreated fly ash indicating the improvement of the fly ashes-UP interaction.